Promoción y prevención de salud bucal mediante propuestas didácticas en niños con síndrome de Down en la Unidad Educativa de Educación Especializada Ciudad de Loja Nº 1 durante el periodo septiembre 2019 - marzo 2020 - Tenezaca González, Lizeth María (2020)
Currently in our city doesn´t exist a promotion and prevention program of oral health focused on children with Down syndrome, showing the lack of information and correct training of future dentists and caregivers of said population. By virtue of this, upon discovering the shortcomings is set as objective to improve the knowledge in subjectstate of the bucodental health by a promotion and prevention based in didactic´s proposes to improve the aparatus stomatognathic obtaining a healthier life in children with down syndrome in the ¨Educational Unit of Specialized Education Ciudad de Loja Nº 1¨during the period September 2019 - March 2020. Being a descriptive, observational and cross-sectional study, it was aplicated the didactic propose in 33 children with Down syndrome, of which 17 childrens had moderated intelectual disability and 16 light intelectual disability. By applying the poll to recollect the data, it could identify an improvement in the knowledge of the children, passing of a deficient knowledge to an excellent knowledge in the Likert scale. In this way it was verified that, by applying the didactic proposal such as models , pictograms, music and dynamic talks for short periods of time, you will reach a much more concrete understanding of oral health. Is like this that, is urgent the creation of a program directed especifically to people with phisical and intelectual disability, wich allows let a corret interpretation, understanding and learning in theme of oral health, focused on improving their health habits, and prevention of future illnesses. Key words: dentistry, pediatric dentistry, syndrome, disability, inclusion.